Study of serum lipid profile and magnesium in preeclampsia - Reddy, Hymavathi K.; P., Vineela; Chowdary, Bhargavi M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: A comparative study of serum lipid profile and magnesium levels in normal pregnancy versus preeclampsia (PE). Methods: A prospective study done for 2 years (October 2014 to October 2016) in the Department of Obstetrics and Gynecology, Narayana medical college and hospital, a tertiary care centre, Nellore, Andhra Pradesh, India. A sample size of 200 pregnant women, recruited and divided into group A and B. group A being women with PE and group B is normal pregnant women.A10ml of venous blood was collected in the fasting state and serum collected from clotted blood to measure lipid profile, magnesium, Apo lipoprotein A-I and Apo lipoprotein B 100.Serum Lipid profile measured by enzymatic method using commercially available kit Human (GmbH Germany) using humastar 600 chemistry analyzer (Human GmbH Germany). Serum magnesium measured by dye binding method using commercially available kit Human (GmbH Germany) using Humastar 600 chemistry analyzer (Human GmbH Germany). Serum ApoA-I and ApoB were measured by immune-turbidometry using commercial kits from Spinreact Spain. Urine albumin done by dipstick method. Results: Serum total cholesterol (TC), Triglyceride (TG), low density lipoprotein (LDL), very low-density lipoprotein (VLDL), Apo lipoprotein B 100 (Apo B100) were high and serum Magnesium, high density lipoprotein (HDL) and Apo lipoprotein A1(Apo A1) were low in the study group (group A) compared to controls (group B). Conclusions: Abnormal lipid profile (low HDL and increased TG concentration) and serum hypomagnesaemia may be contributing etiologies of preeclampsia, having good predictive value as a screening procedure for PE in high risk pregnant population.